2018
DOI: 10.1080/14786419.2018.1475376
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary ammonium compounds in roots and leaves of Capparis spinosa L. from Saudi Arabia and Italy: investigation by HPLC-MS and 1H NMR

Abstract: Capparis spinosa L. is a perennial plant typical of the Mediterranean flora and a multipurpose plant used for curing various human ailments. Quaternary ammonium compounds (QACs), as constituents of Capparaceae, play important roles in protecting against abiotic stress. Aim of this work was to determine QACs in root and leaves of caper from two proveniences. The presence of stachydrine, choline, glycine betaine and homo-stachydrine has been confirmed by high resolution MS, while H NMR was applied to quantify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…[13,47] In another study, stachydrine, a quaternary ammonium compound, was quantified at 20.2 mg/g and 32.3 mg/g of dry leaves of C. spinosa L. from South Italy and Saudi Arabia, respectively, while smaller content of stachy- drine was quantified in dry roots (from 10.4 to 12.5 mg/g). [48] In the same study, choline, another quaternary ammonium compound, was also found in dried leaves and roots of C. spinosa L. but in considerably lower quantities (from 0.3 to 1.2 mg/ g). [48] Several common glucosinolates, such as glucocapparin, isopropyl/n-propyl-glucosinolates, glucobrassi- cin, and 4-hydroxyglucobrassicin, have been found in C. spinosa L. [49] The uncommon two sulfur-rich glucosinolates 5 and 6 (Figure 2) were found in the buds' extract.…”
Section: Isolated Compounds From C Spinosa Lmentioning
confidence: 82%
See 2 more Smart Citations
“…[13,47] In another study, stachydrine, a quaternary ammonium compound, was quantified at 20.2 mg/g and 32.3 mg/g of dry leaves of C. spinosa L. from South Italy and Saudi Arabia, respectively, while smaller content of stachy- drine was quantified in dry roots (from 10.4 to 12.5 mg/g). [48] In the same study, choline, another quaternary ammonium compound, was also found in dried leaves and roots of C. spinosa L. but in considerably lower quantities (from 0.3 to 1.2 mg/ g). [48] Several common glucosinolates, such as glucocapparin, isopropyl/n-propyl-glucosinolates, glucobrassi- cin, and 4-hydroxyglucobrassicin, have been found in C. spinosa L. [49] The uncommon two sulfur-rich glucosinolates 5 and 6 (Figure 2) were found in the buds' extract.…”
Section: Isolated Compounds From C Spinosa Lmentioning
confidence: 82%
“…[48] In the same study, choline, another quaternary ammonium compound, was also found in dried leaves and roots of C. spinosa L. but in considerably lower quantities (from 0.3 to 1.2 mg/ g). [48] Several common glucosinolates, such as glucocapparin, isopropyl/n-propyl-glucosinolates, glucobrassi- cin, and 4-hydroxyglucobrassicin, have been found in C. spinosa L. [49] The uncommon two sulfur-rich glucosinolates 5 and 6 (Figure 2) were found in the buds' extract. [49] Two new compounds 3-methyl-2-butenyl-βglucoside and β-sitosterylglucoside-6'-octadecanoate were also isolated from C. spinosa L. of Jordanian origin.…”
Section: Isolated Compounds From C Spinosa Lmentioning
confidence: 82%
See 1 more Smart Citation
“…Edgew., [21] and Buchholzia coriacea Engler; [22] whereas Capparis dongvanensis and Buchholzia coriacea also produce stigmasterol [19,22] . For what concerns betaine alkaloids, they have been detected in Maerua juncea Pax, Maerua schinzii Pax and Capparis spinosa L., among others [23,24] . Finally, we can mention rhamnetin, isorhamnetin, their derivatives and other flavonoids, that can be found in many Capparis species, such as C. spinosa var.…”
Section: Introductionmentioning
confidence: 99%
“…C. spinosa has been traditionally used in Uygur medicine for 1000 of years for the treatment of difficult diseases such as paralysis, limb numbness, and joint pain caused by cold and dampness 1 . The main chemical components of C. spinosa are quaternary ammonium alkaloids (such as betaine and stachydrine), flavonoids, glucosinolates, fatty acids, polysaccharides, and volatile substances 2 . Modern pharmacological studies showed that C. spinosa extract has anti‐oxidant, hypoglycemic, antibacterial, anti‐inflammatory, and anti‐allergic biological activities 3,4 .…”
Section: Introductionmentioning
confidence: 99%